2017
DOI: 10.1021/acs.jafc.7b03679
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of the Herbicide Benzobicyclon Hydrolysate in a Model California Rice Field Soil

Abstract: The herbicide benzobicyclon (BZB; 3-(2-chloro-4-(methylsulfonyl)benzoyl)-2-phenylthiobicyclo[3.2.1]oct-2-en-4-one) has recently been approved for use on California rice fields by the United States Environmental Protection Agency (U.S. EPA). Hydrolysis of BZB rapidly forms the active compound, benzobicyclon hydrolysate (BH), whose fate is currently not well understood. A model California rice soil was used to determine BH soil dissipation. The pK and aqueous solubility were also determined, as experimental valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Williams and Tjeerdema (2016) reported that water pH, temperature, and the presence of dissolved organic carbon affects conversion of benzobicyclon to benzobicyclon hydrolysate. Williams et al (2017) observed a decrease in benzobicyclon hydrolysate loss under flooded rice field conditions compared with nonflooded conditions, and higher temperatures increased benzobicyclon hydrolysate dissipation. However, control of Schoenoplectus juncoides (Roxb.)…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Tjeerdema (2016) reported that water pH, temperature, and the presence of dissolved organic carbon affects conversion of benzobicyclon to benzobicyclon hydrolysate. Williams et al (2017) observed a decrease in benzobicyclon hydrolysate loss under flooded rice field conditions compared with nonflooded conditions, and higher temperatures increased benzobicyclon hydrolysate dissipation. However, control of Schoenoplectus juncoides (Roxb.)…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, benzobicyclon hydrolysate is expected to have excellent phloem mobility (ion trapping) (Hsu and Kleier 1996) and has a predicted distribution coefficient (log D; i.e., log K ow plus pK a ) value of −1.5 at pH 7.4, which is similar to that of other triketone and pyrazole HPPD-inhibiting herbicides (0.58 > log D > −1.45 at pH 7.4) (Gandy et al 2015). However, benzobicyclon hydrolysate is ionizable (pK a 2.89) (Williams et al 2017) and will be negatively charged in spray solution and flood water; thus, it will have difficulty crossing the cuticle. In this study, benzobicyclon with or without adjuvants had little activity when spray droplets came in direct contact with leaf foliage, but the addition of an oil-based adjuvant, especially MSO, was necessary to optimize the activity of benzobicyclon when spray droplets came in contact with foliage and flood water.…”
Section: Amazon Sprangletopmentioning
confidence: 89%
“…Similar observations for other pesticides have also been reported. 6,13,33 Additionally, degradation under sterilized conditions may be attributed to the recovery of soil microbes and enzymes aer autoclaving, 34,35 as well as abiotic degradation. Overall, biological degradation is a major mechanism for BIT dissipation in the soil, which is mediated by soil microbes capable of degrading BIT and assisted by abiotic processes.…”
Section: Degradation Of Bit In Soilsmentioning
confidence: 99%